Should physicians always rely on estimated glomerular filtration rate without knowing the equation? - Fabbian F; Priori D; De Giorgi A (Clinical Interventions in Aging, 2017)
Fabio Fabbian, Dario Priori, Alfredo De Giorgi Department of Medical Sciences, Clinica Medica Unit, University Hospital St Anna, University of Ferrara, Ferrara, ItalyWe read with interest the paper written by Deskur-Smielecka et al1 who investigated the performance of three equations for valuating renal function in 174 patients, aged 78 years, with different cancer diagnosis. They used Cockcroft–Gault (C–G), Modification of Diet in Renal Disease (MDRD), and Berlin Initiative Study1 (BIS1) equations and found that there is a considerable disagreement between renal function estimation formulas. We also performed two studies evaluating different formulas for the calculation of glomerular filtration rate (GFR) in patients with eating disorders2 and in those with type 2 diabetes mellitus (DM).3Authors’ replyEwa Deskur-Smielecka1,2 Aleksandra Kotlinska-Lemieszek1,2 Jerzy Chudek3,4 Katarzyna Wieczorowska-Tobis1,2The letter from Fabbian et al, in general, supports our findings concerning the disagreement between currently used equations for the estimation of glomerular filtration rate (GFR). We agree that disagreement in the estimation of kidney function was previously found by a number of authors. However, in our paper1 we describe this aspect in very specific population – geriatric, palliative care patients – with high prevalence of cachexia and substantial muscle mass loss. Our group has shown some similarities (low creatinine generation) to the group of patients with anorexia nervosa and bulimia nervosa studied by Fabbian et al.2 However, it has to be stressed that patients with anorexia nervosa and bulimia nervosa were much younger, and therefore had much better, mostly normal kidney function. The second population analyzed by Fabbian et al3 – diabetic patients – also differ from out cohort, as they were better nourished. Regardless of these differences, the conclusions concerning the disagreement of different methods in the estimation of kidney function are quite similar. Importantly, the disagreement is more clinically significant in older population, including geriatric, palliative care patients, due to much greater prevalence of chronic kidney disease (CKD)4 that affects adjusting drug dosage.View the original paper by Deskur-Smielecka and colleagues.